Polymer electrolyte fuel cells using nafion-based composite membranes with functionalized carbon nanotubes - Kannan, Ramaiyan; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Angewandte Chemie-International Edition, 2008)
Keywords: fuel cells; membranes; nanotubes; Polymers; proton transport

Porous Co3O4 nanorods as superior electrode material for supercapacitors and rechargeable Li-ion batteries - Vijayanand, S.; Kannan, Ramaiyan; Potdar, H. S.; Pillai, V. K.; Joy, Pattayil Alias (Journal of Applied Electrochemistry, 2013)
Porous aggregated nanorods of Co3O4 with a surface area of similar to 100 m(2) g(-1) synthesized without using any templates or surfactants give very high specific capacitance of similar to 780 F g(-1) when used as electrode in a faradaic supercapacitor, with a cycle life of more than 1,000 cycles. Further, in Li-ion batteries when used as an anode, the Co3O4 nanorods achieved a capacity of 1155 mA h g(-1) in the first cycle and upon further cycling it is stabilized at 820 mA h g(-1) for more than 25 cycles. Detailed characterization indicated the stability of the material and the improved performance is attributed to the shorter Li-insertion/desertion pathways offered by the highly porous nanostructures. The environmentally benign and easily scalable method of synthesis of the porous Co3O4 nanorods coupled with the superior electrode characteristics in supercapacitors and Li-ion batteries provide efficient energy storage capabilities with promising applications.
Keywords: Cobalt oxide; Electrode materials; Li-ion battery; Porous nanostructures; supercapacitor